Compartilhamento de risco na América Latina (Economia Aplicada, 2009)
This work sought to characterize the risk sharing in Latin America, utilizing income and consumption per capita of 18 latin american, 6 developed and 11 emerging countries, over the period of 1951-2003. The methodology used data in panel, cointegration and error-correction model. Observed that the risk sharing in Latin America, in general, is low. Intra Latin America, it was 20% in short term and 7% in long term. Intra Latin America and inter developed countries, 15% in short term and 4% in the long term. Intra Latin America and inter developed countries plus the emergent ones, 15% in short term and 13% in the long term. By results, a bigger financial integration of Latin America, intra and intercountries, more specifically with emerging countries, would promote bigger smoothing of its consumption.